Intervensi Kerja Kumpulan Dalam Kalangan Wanita Yang Mengalami Keganasan Rumah Tangga Di Indonesia - Subardhini, Meiti (2013)
Domestic violence is a social problem that has a negative psychosocial impact on women's physical, psychological and social. The main objective of the study was to assess the extent of social work intervention through group work that can enhance the social wellbeing of women who have experienced domestic violence in the city of Bandung. This study focused on the process of problem solving in the context of the work undertaken by a social worker on women who experience domestic violence. Several phases have been identified in this study to enable the social work with group successfully implemented. The first phase was the pre planning that includes the selection of members among women who have been involved in domestic violence. The second phase was the beginning group work intervention that involves the introduction of members to the group work, the formulation of objectives and social norms that must be agreed and observed by members. The third phase was the middle phase that involves activities that should be implemented based on the objectives of the group work. The last phase was the termination phase that allows social worker to assess to what extent the impact of the group's work on women who have experienced domestic violence. This study also focused on the learning outcomes and the impact of social work intervention with small group. A qualitative research based on social action was used for the study. A total of twelve (12) sessions were given to the group intervention and each intervention took about two hours for the group to discuss matters related to domestic violence.